MANAJEMEN PAKAN KUDA DALAM USAHA JASA KUDA KELILING PANTAI DI LOMBOK (HORSE FEED MANAGEMENT IN THE MOBILE HORSE SERVICE BUSINESS AT LOMBOK BEACH) - Harmayani, Ria; Alimuddin, Alimuddin; Fitriyah, abyadul; Aminah Zaim Alyamini, Ishmah Humaidatul; Risfianty, Dwi Kartika; Haekal, Muhammad Haekal (Universitas Muara Bungo, 2025)
The Mobile horse service business at Lombok Beach has the potential to increase local community income and support sustainable tourism. Its success heavily depends on effective feed management, as feed influences horse health and performance. This study analyzes feeding patterns, factors influencing feed selection, and their impacts on horses in the Lombok Beach area. The methods used include direct observation, interviews, questionnaires, and feed testing at 13 locations over three months. The results show that feed is usually provided twice daily in the form of forage and concentrate, with most respondents giving 8-12 kg per horse per day, consisting of grinting grass, udel-udelan spear grass, spear grass, merakan grass, and field grass. Concentrates range from 1 to 3 kg per horse per day, but challenges include the supply of quality forage and high costs. Less optimal feed management increases the risk of parasitic diseases and decreases horse performance. Sustainable efforts include developing feed from agricultural waste, training, partnerships, and waste management and fermented feed practices. It is recommended that farmers/ managers and policymakers strengthen innovation, training, and health monitoring to support the sustainability of this business.Keywords: Beach touring horses, Feed management, Horse feed, Horse health, Horse service business, Horseback riding tourism.